Mummy & me bake - Palosuo, Laura Carrie; Heap, Will; Smart, Denise (London Dorling Kindersley, 2015)
This is the perfect way to learn how to bake together. From icing biscuits to making pizza people, Mummy & Me: Bake helps you and your child learn how to make delicious biscuits, follow mouth-watering cupcake recipes and discover how to bake a cake as a family with this easy-to-follow kids' cookbook, as well as introducing your child to basic baking know-how such as kneading and mixing. Whip up yummy fruit-filled baskets, scrummy cheese tarts, and delicious Italian bread together. Get to know important baking skills such as weighing different ingredients and lining baking dishes, plus using measurements and amounts associated with cooking. Help your child follow the clear step-by-step instructions and pictures to bake beautiful cakes, breads and much more. Children and parents alike will be educated and entertained as they explore the wonderful world of baking with kids. So, get the family together in the kitchen and have fun with food with Mummy & Me: Bake
Cooking
1
Keywords: Baked products -- Juvenile literature; Baking -- Juvenile literature